Hipocrisia de marca e as respostas comportamentais dos consumidores - Rodrigues, Marcos Aurélio Oliveira (2024)
The dissertation investigates consumer perception and responses to brand hypocrisy, an inconsistent and manipulative organizational practice that leads the market to believe in unrealistic benefits of its products and services. The general objective of the research is to identify the relationship between the perception of brand hypocrisy, attitudes, and consumers' behavioral response intentions, with a focus on the healthy food sector. Using a descriptive and quantitative approach, the research employs a survey based on standardized questionnaires with validated scales. Data collection is conducted through an online form applied to individuals with completed or ongoing higher education. The data are analyzed using structural equation modeling (SEM) and moderation techniques to examine cause-and-effect relationships. The results indicate that the perception of brand hypocrisy negatively affects the cognitive and affective dimensions of consumers, leading to behavioral responses such as brand distancing and negative word of mouth, aligning with the SOR model. Moreover, nutritional awareness was identified as a relevant moderator in the relationship between the perception of brand hypocrisy and the affective properties of attitudes. These findings highlight the complexity of consumer responses and provide insights for brand management strategies. The study presents practical implications for brand management, emphasizing the need for coherence between promises and actions, transparency in communication, and genuine social responsibility. Additionally, it contributes to the academic literature by exploring the construct of revenge desire, expanding the understanding of consumer behavioral responses in a different cultural context.